The 12 pillars of project excellence : a lean approach to improving project results - Dalal, Adil F. (Productivity, 2011)
Asking tough questions about the current state of project management, The 12 Pillars of Project Excellence: A Lean Approach to Improving Project Results provides groundbreaking techniques to achieve excellence in project leadership that can result in six sigma type results or failure-free projects. It unveils novel solutions and breakthrough concepts--including project culture analysis, the five powers of project leadership, the power of visualization™, the science of simplicity™, dynamic risk leadership, and dynamic project failures analysis--to help you chart the most efficient path to the pinnacle of project leadership. Winner of a 2013 Axiom Business Book Award The author provides the cutting-edge methods based on decades of personal practical experience, valuable lessons learned, and authoritative insights gained from leading over 300 projects to successful conclusions. Complete with powerful tools for organizational- and self-assessment on the accompanying CD, this book will not only transform your approach to project management, but will also provide you with the tools to develop effective leaders and consistently achieve exceptional business results. Some Praise for the Book: ... a highly pragmatic guide to project management. ... lays out the way of thinking that underpins success... a book that everyone could benefit from.--Mikel J. Harry, Ph.D., co-creator of Six Sigma provides the most significant contribution for leaders to mitigate project risks, assure sustainable growth, and guarantee survival... .--Carlos Alberto Briganti, general manager of Eaton Europe and Japan, 2001-2003; vice president of Eaton South America 2004-2007 ... one of the BEST books I have ever read on project leadership.--John Salazar, CIO Department of Work Force Solutions; former CIO of Department of Taxation & Revenue, State of New Mexico ... a comprehensive guide that will assist any business leader within an organization to consistently achieve excellent business results! A '--Billy Billimoria, director, customer applications, BAE Systems; program director, Lockheed Martin; project engineer, Space Shuttle and Support Equipment Design must buy'--get it now!.